1999
DOI: 10.1038/sj.ejcn.1600889
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplements of dehydroepiandrosterone in relation to breast cancer risk

Abstract: Objective: Dietary supplements of the adrernocertical hormone dehydroepiandrosterone (DHEA) are widely taken in the hope of staving off the aging process. Potential dangers have not been fully researched, particularly evidence of a correlation between increased serum concentrations of DHEA and higher breast cancer risk in postmenopausal women. Design: The review examines reports of clinical, epidemiological experimental studies for evidence that DHEA may be a factor in promoting the growth of mammary cancer. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Thus, mild acne, hirsutism, and oiliness of the skin have been noted in women [157]. There continues to be concern over possible stimulation of hormone-dependent neoplasia, including breast and prostate [158,159]. Apart from these hormonal effects there are some reports of psychiatric manifestations of DHEAS use [160].…”
Section: Molecular Mechanisms Of Dhea(s) Action: Putative Plasma Membmentioning
confidence: 92%
“…Thus, mild acne, hirsutism, and oiliness of the skin have been noted in women [157]. There continues to be concern over possible stimulation of hormone-dependent neoplasia, including breast and prostate [158,159]. Apart from these hormonal effects there are some reports of psychiatric manifestations of DHEAS use [160].…”
Section: Molecular Mechanisms Of Dhea(s) Action: Putative Plasma Membmentioning
confidence: 92%
“…In vitro data suggest that DHEA and DHEAS inhibit breast cell proliferation possibly through epidermal growth factor (26), although they can stimulate proliferation, especially in a low-estrogen environment (1,3,22,24,25). Thus, DHEA and DHEAS may act as estrogen antagonists in a high estrogen environment, but act as weak estrogen agonists in a low-estrogen environment (1,2,27). A second hypothesis posits that women who develop breast cancer have a blunted age-related decline in DHEA and DHEAS levels (1,17,28,29); that is, compared with healthy controls, women who develop breast cancer in early-to midpremenopausal years have similar or lower DHEA or DHEAS , family history of breast cancer (yes, no), age at menarche (<12, 12, 13, z14 years), history of benign breast disease (yes, no), and parity/age at first birth (nulliparous, age at first birth <25 years/1-2 children, age at first birth 25 to 29 years/1-2 children, age at first birth z30 years/1-2 children, age at first birth <25 years/z3 children, age at first birth z25 years/z3 children).…”
Section: Discussionmentioning
confidence: 99%
“…DHEA also inhibited the development of tumors of the rat testis (Rao et al, 1992b) and rat and mouse mammary gland (Schwartz et al, 1981;McCormick et al, 1996). A recent review of clinical, experimental, and epidemiological studies concluded that late promotion of breast cancer in postmenopausal women may be stimulated by prolonged intake of DHEA (Stoll, 1999); however, the evidence for a positive association in postmenopausal women between serum DHEA levels and breast cancer risk is conflicting (Bernstein et al, 1990;Stoll, 1999). Natural Pesticides Natural pesticides, because few have been tested, are markedly underrepresented in our HERP analysis.…”
Section: The Herp Ranking Of Possible Carcinogenic Hazardsmentioning
confidence: 91%